2004
DOI: 10.1038/ng1331
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific repression of lymphotoxin-α by activated B cell factor-1

Abstract: Genetic variation at the human LTA locus, encoding lymphotoxin-α, is associated with susceptibility to myocardial infarction, asthma and other diseases. By detailed haplotypic analysis of the locus, we identified a single-nucleotide polymorphism (SNP) at LTA+80 as a main predictor of LTA protein production by human B cells. We found that activated B-cell factor-1 (ABF-1) binds to this site in vitro and suppresses reporter gene expression, but only in the presence of the LTA+80A allele. Using haplotype-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
4
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 30 publications
2
69
4
1
Order By: Relevance
“…The LTA þ 77 SNP has been reported to affect LTA protein production in human EBV-transformed B cells. 31 The functionality of the risk þ 77T allele is thought to reside in the fact that the activated B cell Factor-1 (ABF-1) only binds in the presence of this low producing þ 77T allele in vivo to suppress gene expression. 31 Conversely, the LTA þ 252G allele, present in HAP2 and HAP3 but absent in HAP1, has been linked to higher LTA transcription levels in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LTA þ 77 SNP has been reported to affect LTA protein production in human EBV-transformed B cells. 31 The functionality of the risk þ 77T allele is thought to reside in the fact that the activated B cell Factor-1 (ABF-1) only binds in the presence of this low producing þ 77T allele in vivo to suppress gene expression. 31 Conversely, the LTA þ 252G allele, present in HAP2 and HAP3 but absent in HAP1, has been linked to higher LTA transcription levels in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…31 The functionality of the risk þ 77T allele is thought to reside in the fact that the activated B cell Factor-1 (ABF-1) only binds in the presence of this low producing þ 77T allele in vivo to suppress gene expression. 31 Conversely, the LTA þ 252G allele, present in HAP2 and HAP3 but absent in HAP1, has been linked to higher LTA transcription levels in vitro. 13,14 Our data support the suggestion from in vitro functional studies of independent and opposite functional effects for LTA þ 77 T and þ 252G.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we agree that replication/validation of those LTA SNPs in larger, well-designed studies within genetic and functional framework is critical. Knight et al (2004) had identified the A allele of A+80C polymorphism as a main predictive variable of LTA protein production by a detailed haplotype analysis of TNF/ LTA locus. Contrarily, we did not find a significant singlelocus association between CAD and A+80C polymorphism, which was one of the SNPs harboring the protective haplotype G-C-T-C.…”
Section: Discussionmentioning
confidence: 99%
“…For genes without transcribed genetic markers, relative allelic expression can be assessed by haplotype-specific chromatin immunoprecipitation (haploChIP) for RNA polymerase II using antibodies specific for the phosphorylated serine residues in the C-terminal domain characteristic of actively transcribing RNA polymerase II [135]. This approach can also be used to resolve allelespecific recruitment of specific transcription factors such as activated B cell factor-1 which we demonstrated was recruited to the LTA (encoding lymphotoxin alpha) gene [136] in the presence of a genetic variant subsequently associated with susceptibility to leprosy [137].…”
Section: Allele-specific Gene Expressionmentioning
confidence: 99%